Clinicopathological differences in the activation pattern of the complement system between pediatric and adult lupus nephritis: a single centered retrospective study in Korea - Min Ji Park; Man Hoon Han; Mee-seon Kim; Yong-Jin Kim; Sang Jin Lee; Dongsub Kim; Hee Sun Baek; Min Hyun Cho (Childhood Kidney Diseases)
Purpose Lupus nephritis (LN) can be caused by the complement activation. This study aimed to investigate the differences and clinical implications of the activation pattern of the complement system for pediatric and adult LN patients. Methods We retrospectively reviewed the medical records of 40 patients (14 pediatric and 26 adult patients) diagnosed with LN through kidney biopsy. Results The mean ages at diagnosis of pediatric and adult patients were 11.7±2.92 and 37.3±13.5 years, respectively. At the first LN diagnosis, compared with adult patients, pediatric patients had a higher estimated glomerular filtration rate and milder proteinuria; however, there was no statistical significance. The age-adjusted mean serum complement 3 value was significantly lower in the pediatric group (33.0±11.3 mg/dL) than in the adult group (50.8±25.2 mg/dL) (P<0.01). Based on the findings of kidney biopsy, no significant differences were observed in the severity of pathologic classification and the positive rate of complements between adults and children. However, the chronicity index score of adult patients was significantly higher than that of pediatric patients and in the case of complement 4d, despite a similar positive rate, the intensity was significantly stronger for adults (2.35±0.83 vs. 1.54±0.52, P=0.04). Conclusions The activation pattern of the complement system in LN differs clinicopathologically between pediatric and adult patients and these differences might play an important role in the age-dependent prognosis of LN.